BLUSHED! MAKE-UP AND SONG NARATIVE CONHERENCE IN THE MUSIC VIDEOS OF TAYLOR SWIFT AND OLIVIO RODRIGO - Siti Mustaghatsah Birahmatika; Deswita Ayu Nabilah; Luluk Suparwati (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study explores the role of make-up as a narrative device in the music videos of Taylor Swift and Olivia Rodrigo, emphasizing its contribution to narrative coherence within Walter Fisher’s Narrative Paradigm framework. Using a qualitative descriptive approach and multimodal discourse analysis, the research examines how make-up interacts with lyrics, visuals, and emotional tone to construct structural, material, and characterological coherence. The findings reveal that make-up functions not merely as an aesthetic element but as a visual code that reinforces emotional authenticity, character transformation, and thematic unity. In Taylor Swift’s videos, make-up signifies shifts in identity, emotion, and empowerment, while in Olivia Rodrigo’s works, it mirrors emotional evolution and self-awareness. Through this interplay, make-up emerges as a key multimodal element that bridges visual aesthetics and narrative meaning, enhancing audience engagement and sustaining coherence in contemporary pop music storytelling. Building on these insights, future research could further explore the symbolic and cultural dimensions of make-up across visual media, examining how make-up, costume, and lighting shape identity representation, emotional expression, and social commentary in digital and participatory environments.